Inter-generation interaction app - Azmira Tania (2015)
In today’s world, technology is being globally embraced by everyone, from the older generation all the way to the young. While technology has proven to be advantageous in the political and economic spheres, it has only managed to inspire superficial social connections, and worse, it has made the interaction between generations limited and strained. The current market only provides a limited number of options in this area and the most lacking of all media forms in fostering intergenerational interaction is in the area of smartphone applications. This paper proposes an Android application, which aims to bridge the gaps between generations within a family using technology to improve interaction while also being an interactive and user-friendly application for all generations. The application, Lucky Family, is designed to facilitate wholesome interactions when the family unit is physically apart from one another. It is intended to complement face-to-face interactions. Gamification has been incorporated in the making of Lucky Family. This involves adding elements of a game such as point systems, badges, leader boards or game design patterns into non-gaming contexts. The target audience for this application are families with at least three different generations. It is a collaborative application that aims to positively affect change by enhancing intergenerational interaction in a manner that is natural and encouraging.